Percepción de los agricultores y productores pecuarios sobre el agroturismo en el cantón Vinces - Díaz Rendon, Jerry Humberto (2023)
In the context of the Vinces canton, a study has been carried out to understand the perception of farmers and livestock producers about agrotourism. The main objective of this research, which followed a descriptive and quantitative approach, was to describe the agrotourism perception in the Vinces canton. For this, a survey was applied as the main data collection technique. The results obtained reveal solid support for agrotourism in the Vinces canton. Most participants show a clear willingness to consider agritourism as a potential source of income. However, digging deeper into the data reveals diverse perspectives among respondents. One group considers that this activity can improve the image of the agricultural sector, while another values the opportunity to acquire new knowledge through agrotourism. However, challenges such as lack of technical training and limited infrastructure remain, highlighting the need to invest in training programs and infrastructure improvement to ensure successful development of this industry.